Macro-Micromechanical Properties of Sandy Pebble Soil of Different Coarse-Grained Content (2018)
Sandy pebble stratum is a typical discrete particle unstable stratum, mainly consisting of sand and pebble. However, the effect of coarse-grained content on the stability of stratum is not clear. This paper defined the sandy pebble soil of different coarse-grained content in Chengdu City, Sichuan Province, China as the research object. Research on macro-mesomechanical properties of sandy pebble soil of different coarse-grained content was carried out using the method combining the indoor large-scale triaxial test of coarse-grained soil with the discrete element numerical triaxial test. The research results showed that the stress-strain curve of sandy pebble soil exhibited strain softening with the increase of coarse-grained content; when the confining pressure was the same, the stress peak increased and the strain when the peak was reached decreased gradually with the increase of coarse-grained content. It revealed the functional relationship between coarse-grained content and mechanical indexes of sandy pebble soil such as internal friction angle and cohesion. The internal friction angle and cohesion of sandy pebble soil linearly increased with the rise of coarse-grained material; it proposed the particle discrete element micro parameters of sandy pebble soil of different coarse-grained content, including contact modulus, friction coefficient, particle stiffness ratio, contact bond strength. The research results provided the theoretical support for the new design and construction of sandy pebble stratum project.